Masculinity of Arthur Dismmesdale in the Novel the Scarlet Letter by Nathaniel Hawthrone - Yanti, Cita Hikmah; Pane, Chairunnisah (IJLECR (International Journal of Language Education and Cultural Review), 2024)
Finding masculinity in a character represented in a novel enables to investigate more to understand social behavior as social issue in personal or in a certain community. This study aims to find the masculinity in the character of Arthur Dismmesdale, a puritan priest in the novel of the scarlet letter that attract the writer to identify the uncommon manner of a male character. His character also viewed as one of influencing character who undergo social and psychological traits into the story which led the other main character took the blame on his behalf. This study was researched descriptively by reducing data and data grouping based on the problem studied. Data were taken from words and sentenced in the novel then describe and explain of character’s personality using Sigmund Freud Psychoanalysis that is id, ego and analyzing Masculinity. Arthur Dimmesdale, A concealed sinner, has a very complicit nature in masculinity, this is due to his inability to be a responsible towards his evil deeds. The character was indicated as dynamic character, He cursed himself for his silence and cowardice yet changed structurally during the story and complexed the whole story.